Pengajaran IPS: Antara Gagasan Dan Pelaksanaan Di SMPN Kota Padang - Etmi Hardi; Wahidul Basri (Diakronika, 2018)
Integrated social studies learning has begun to be applied in various middle school (Sekolah Menengah Pertama) in Padang, especially since 2007. The principle of integration is integrating four fields of study, namely geography, economics, history and sociology into a certain theme. Integrated learning, firstly stated in the 2013 curriculum ideally, but in practice, it was different. Teachers at schools still cannot fully implement the Integrated Social Studies learning as appropriate, including SMP in Padang city. The purpose of this study is to see how Social studies which are in the Public Middle School in Padang. This research was conducted in several junior high schools in Padang. 8 of 43 public junior high schools in Padang to be the research subject, choose randomly, namely SMPN 1, SMPN 2, SMPN 6, SMPN 7, SMPN 8, SMPN 15, SMPN 16, dan SMPN 35. Data were collected through interviews with some social studies teachers, the Ministry of Education in Padang, and education observers in Padang. Research data was also collected through studies documentation and direct observation in class. The result shows that most social studies teachers at Padang in Junior High School not yet able to carry out Integrated Social Studies learning. There are still weaknesses in the selection of learning models which can support social studies learning, media and source selection improper learning.